Analysis Of Dominant Risks Affecting Time Performance Based On The Work Breakdown Structure (WBS) Of Deep Soil Mixing (DSM) Works - Alisya Salsabila Putriedi; Rully Andhika Karim (CV. AFDIFAL MAJU BERKAH, 2026)
Deep Soil Mixing (DSM) work is a soil improvement method widely used in construction projects on soft soil. Although effective in improving the geotechnical characteristics of the soil, DSM implementation still faces various risks that have the potential to cause project delays. This study aims to identify and analyze the dominant risks that affect the time performance of DSM work based on the Work Breakdown Structure (WBS) approach. The study used a mixed method, namely a qualitative approach for the preparation and validation of the WBS through the Delphi method involving five experienced experts in the field of Soil Improvement, and a quantitative approach for risk analysis using the Severity Index (SI). The results of the study produced a WBS structure for DSM work up to Level 6 consisting of work packages, implementation methods, activities, and resources. Based on the risk mapping in the WBS, 51 risk variables were identified that have the potential to affect the time performance of the project. The risk analysis showed that there were 12 dominant risks with a high risk category. The main risks include Unconfined Compressive Strength (UCS) results that do not meet specifications, low labor quality, curing wait time, variability in soil conditions, working platform instability, delays in material delivery, and equipment damage. The results of the study show that the implementation of WBS-based risk management can help systematically identify risks and support improved time performance in DSM work.